Effect of mode shift from car to light rail on personal exposure: A controlled experiment. (January 2019) - Hong, Andy
Abstract: Light rail transit (LRT) has a reputation for being cleaner and healthier than automobiles. However, few studies have examined the effects of mode shift from automobile to LRT. This paper investigates to what extent mode shift from car to LRT can reduce personal exposure to PM2.5, BC, and UFP. Simultaneous measurements on LRT and automobile were conducted under four plausible commuting scenarios in Los Angeles, California from October to November in 2014. As a robustness check, Monte Carlo simulations were performed to test the effects of confounding factors. Under the closed ventilation and low traffic condition, personal exposure measurements inside LRT were significantly higher than in automobile for BC (+40%, p  < 0.01) and UFP (+27%, p  < 0.01). However, under the open ventilation and high traffic condition, personal exposure was significantly lower in LRT than in automobile for PM2.5 (−38%, p  < 0.01); BC (−68%, p  < 0.01); and UFP (−141%, p  < 0.01). Results of the Monte Carlo simulations suggest that other factors, such as vehicle fan strength, vehicle speed, and vehicle age, appear to have marginal effects on personal exposure. These results demonstrate that the effect of mode shift from car to LRT can be significantly altered by ventilation settings and travel route choices. Results inform future research and policy about the importance of incorporating ventilation and traffic microenvironments for assessing the health effects of a mode switch from car to LRT. Graphical abstract: Image 1 Highlights: Examined the effect of mode shift from car to LRT using simultaneous measurements. Developed Monte Carlo simulations to test the effects of confounding factors. The effect of mode shift was driven by ventilation and traffic condition. Other factors, such as vehicle age, speed, and fan strength, were less influential.